2021
DOI: 10.1051/e3sconf/202125102025
|View full text |Cite
|
Sign up to set email alerts
|

Research on the influence of theme restaurant interior design on users’ consumption behavior based on the layout of interior environment space

Abstract: The traditional research method of user consumption behavior influence is too subjective in the selection of indicators at the time of research, which leads to poor referenceability of research results. To this end, the problems of traditional influence research methods are improved by proposing a method for analyzing the influence of theme restaurant interior design on user consumption behavior based on the spatial layout of the interior environment. On the basis of analyzing user consumption behavior pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Wan [ 7 ] created the influence model of user consumption behavior and selected statistical indicators to finish the research process based on evaluating user consumption behavior patterns and defining factors affecting consumer behavior. The simulation experiment demonstrated that the method's study results can be used to improve restaurant operations and have practical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Wan [ 7 ] created the influence model of user consumption behavior and selected statistical indicators to finish the research process based on evaluating user consumption behavior patterns and defining factors affecting consumer behavior. The simulation experiment demonstrated that the method's study results can be used to improve restaurant operations and have practical relevance.…”
Section: Introductionmentioning
confidence: 99%